Occupational Therapists' Perspectives on Family-Centered Practices in Early Intervention - Irma J. Pereira; Francine M Seruya (Scholarworks @ WMU, 2021)
Background: Early intervention (EI) requires service provision in natural settings while incorporating interventions based on family-centered practice (FCP). This study sought to understand (a) how occupational therapists define and implement FCP in their daily interventions and (b) therapists' perspectives on using this model of practice in EI. Method: This study used a qualitative, phenomenological approach. Nine licensed occupational therapists from six states with a minimum of 3 years of working experience in the area of EI participated. Semi-structured interviews were recorded, transcribed, and subsequently coded and analyzed for emergent themes. Results: The therapists had an average of 12.6 years of experience in EI. Four themes were identified: (a) confusion on meaning and implementation of FCP, (b) FCP creates feelings of insecurity, (c) FCP requires therapists to assume roles and engage in activities or practices for which they are not prepared, and (d) systemic issues affect the ability to implement FCP in EI. Conclusion: The participants reported limited evidence-based practice guidelines on FCP models and emphasized the need for training to have a commonality in defining and implementing FCP. Findings indicate a need to address systemic issues affecting how services are approved, delivered, and funded.